High-temperature-resistant large-temperature-difference low-density cement paste as well as preparation method and application thereof
By preparing a specific high-temperature, large-temperature and low-density cement slurry, the problems of poor stability and shortening of thickening time under high temperature and large temperature differences are solved, and good stability under high temperature and large temperature differences are achieved. Sexual and intensity development.
Patent Information
- Application Number
- CN202411656095.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
AI Technical Summary
The existing low-density cement slurry exhibits poor stability, shortened thickening time and unsatisfactory top strength development under high temperature and large temperature differences.
By formulating a high temperature high temperature difference low density cement slurry including G-grade oil well cement, mitigating agent, filler material, water loss reducing agent, retarder, latex, defoaming agent and water, the ratio of each component is adjusted to Adapt to high temperature and large temperature difference conditions.
Under the conditions of high temperature of 160℃ and large temperature difference of less than 120℃, the cement slurry has good stability, adjustable thickening time, and significantly improved the top strength development speed of large temperature difference, and has low density, low mode resistance, and gas resistance. Advantages such as squirting and increasing elasticity.
Smart Images

Figure BDA0005142146080000151 
Figure BDA0005142146080000152 
Figure BDA0005142146080000161
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oilfield chemistry, and specifically relates to a high-temperature resistant, large-temperature-difference low-density cement slurry and a preparation method and application thereof. Background Art
[0002] As oil and gas exploration and development develops towards deep and complex formations, the number of deep and ultra-deep wells increases, and the problems brought about by high temperature and high pressure, and the easy leakage and collapse of complex formations become more and more obvious. For the cementing of long sealing sections of deep and ultra-deep wells, one-time cementing is often used to avoid the many disadvantages of two-stage cementing. Low-density cement slurry is widely used in cementing operations of long sealing sections of deep and ultra-deep wells. It can effectively reduce the pressure of the liquid column and prevent leakage of the formation. It also has the advantages of low mold resistance and high displacement efficiency.
[0003] The existing low-density cement slurry and its supporting filling materials and admixtures are not specially developed for high temperature and large temperature difference conditions. The performance of the existing low-density cement slurry cannot fully meet the requirements of cementing wells with high temperature and large temperature difference. In particular, the filling materials of low-density cement slurry are generally only suitable for medium and low temperatures, which can easily cause poor stability and shortened thickening time at high temperatures. At the same time, admixtures such as fluid loss reducers are not suitable for cementing conditions with large temperature differences. The performance of existing retarders with large temperature differences is not ideal. The performance of low-density cement slurries used for high temperatures often cannot take into account large temperature difference conditions.
[0004] Therefore, it is necessary to develop oil well cement admixtures and low-density cement materials suitable for high temperature and large temperature difference conditions to form low-density cement slurry that can be used for both high temperature and large temperature difference conditions, and to improve the stability, applicability and large temperature difference performance of low-density cement slurry at high temperature. Summary of the invention
[0005] In view of the defects of the prior art, the present invention provides a high temperature resistant, large temperature difference, low density cement slurry and a preparation method and application thereof.
[0006] The present invention is achieved through the following technical solutions:
[0007] A high temperature resistant, large temperature difference and low density cement slurry comprises: G-class oil well cement, a lightening agent, a filling material, a fluid loss reducing agent, a retarder, latex, a defoaming agent and water.
[0008] The high temperature resistant, large temperature difference, low-density cement slurry comprises, by weight: 100 parts by weight of G-grade oil well cement; 8-35 parts by weight of lightening agent; 8-45 parts by weight of filling material; 5-20 parts by weight of fluid loss additive; 0-10 parts by weight of retarder; 0-20 parts by weight of latex; 0.5-3 parts by weight of defoaming agent; and 50-100 parts by weight of fresh water.
[0009] The above-mentioned high temperature resistant large temperature difference low density cement slurry, the lightening agent is artificial glass microspheres, the pressure bearing capacity of the artificial glass microspheres is 10000-25000psi, and the density is 0.6±0.2g / cm 3 .
[0010] The above-mentioned high temperature resistant, large temperature difference and low density cement slurry, the filling materials are fly ash, microsilicon, ultrafine cement and silicon powder in a mass ratio of 5-25:5-45:5-30:10-55.
[0011] The above-mentioned high temperature resistant large temperature difference low density cement slurry, the density of the fly ash is between 2.0-2.6g / cm 3 The microsilicon has a particle size between 0.05-0.5 μm and a density between 2.0-2.4 g / cm 3 Amorphous silica; the particle size of the ultrafine cement is between 0.5-10 μm and the density is between 2.5-3.2 g / cm 3 The silicon powder has a mesh size between 800-1000 mesh and a density between 2.5-2.8 g / cm 3 Natural quartz powder.
[0012] The above-mentioned high temperature resistant large temperature difference low density cement slurry, the fluid loss reducer is prepared by the following method:
[0013] (1) adding 2-acrylamido-2-methylpropanesulfonic acid, sodium hydroxide, nonionic monomer, carboxylic acid monomer, cationic monomer, crosslinking agent and molecular weight regulator to deionized water in sequence, stirring and mixing, heating and passing inert gas;
[0014] (2) adding ammonium persulfate solution dropwise, and after the reaction temperature stabilizes, heating is continued to react to obtain a fluid loss reducer.
[0015] The above-mentioned high temperature resistant, large temperature difference low density cement slurry, calculated by weight, comprises 100 parts by weight of deionized water; 15-30 parts by weight of 2-acrylamido-2-methylpropane sulfonic acid; 2-10 parts by weight of nonionic monomer; 0.1-5 parts by weight of carboxylic acid monomer; 0.1-5 parts by weight of cationic monomer; 0.001-0.1 parts by weight of crosslinking agent; 0.1-2 parts by weight of ammonium persulfate; 3-10 parts by weight of sodium hydroxide; and 0.1-1 parts by weight of molecular weight regulator.
[0016] In the above-mentioned high temperature resistant, large temperature difference, low-density cement slurry, the non-ionic monomer is one or more of acrylamide, N,N-dimethylacrylamide, N-hydroxymethylacrylamide, and 4-acryloylmorpholine; the carboxylic acid monomer is one or more of acrylic acid, maleic anhydride, and itaconic acid.
[0017] In the above-mentioned high temperature resistant, large temperature difference, low-density cement slurry, the cationic monomer is one or more of methacryloyloxyethyl trimethyl ammonium chloride, methacryloyl propyl trimethyl ammonium chloride, and dimethyl diallyl ammonium chloride; the cross-linking agent is one or more of diacetone acrylamide, N,N-methylenebisacrylamide, pentaerythritol triallyl ether, and trimethylolpropane triacrylate; the molecular weight regulator is one or more of tert-dodecyl mercaptan, isooctyl 3-mercaptopropionate, sodium vinyl sulfonate, sodium methacrylic acid, and sodium formate.
[0018] The above-mentioned high temperature resistant large temperature difference low density cement slurry, the retarder is prepared by the following method:
[0019] (1) adding 2-acrylamido-2-methylpropanesulfonic acid, a rigid monomer, a carboxylic acid monomer, an ether monomer, a crosslinking agent, and a molecular weight regulator to deionized water in sequence, stirring and mixing, heating, and introducing an inert gas;
[0020] (2) adding ammonium persulfate solution and tetraethylenepentamine solution dropwise successively, and after the reaction temperature stabilizes, heating is continued to react to obtain a retarder.
[0021] The above-mentioned high temperature resistant, large temperature difference, low density cement slurry, calculated by weight, comprises 100 parts by weight of deionized water; 15-50 parts by weight of 2-acrylamido-2-methylpropane sulfonic acid; 2-15 parts by weight of the carboxylic acid monomer; 0.5-10 parts by weight of the rigid monomer; 0.1-5 parts by weight of the ether monomer; 0.02-2 parts by weight of the cross-linking agent; 0-5 parts by weight of the molecular weight regulator; 0.2-2 parts by weight of the ammonium persulfate; and 0.2-2 parts by weight of the tetraethylene pentamine.
[0022] In the above-mentioned high temperature resistant, large temperature difference, low density cement slurry, the carboxylic acid monomer is one or more of acrylic acid, maleic anhydride, and itaconic acid; the rigid monomer is one or more of sodium styrene sulfonate, N,N-dimethylacrylamide, and N-hydroxymethylacrylamide.
[0023] In the above-mentioned high temperature resistant, large temperature difference, low-density cement slurry, the ether monomer is one or more of allyl polyoxyethylene ether-1200, allyl polyoxyethylene ether-2400, allyl polyoxyethylene ether-3600, methyl allyl polyoxyethylene ether-1200, methyl allyl polyoxyethylene ether-2400, methyl allyl polyoxyethylene ether-3600, isopentanol polyoxyethylene ether-1200, isopentanol polyoxyethylene ether-2400, and isopentanol polyoxyethylene ether-3600.
[0024] In the above-mentioned high temperature resistant, large temperature difference, low-density cement slurry, the cross-linking agent is one or more of diacetone acrylamide, polyethylene glycol diacrylate-400, trimethylolpropane triacrylate, and ethylene glycol diallyl ether; the molecular weight regulator is one or more of tert-dodecyl mercaptan, isooctyl 3-mercaptopropionate, sodium vinyl sulfonate, sodium methacrylic acid, and sodium formate.
[0025] In the above-mentioned high temperature resistant, large temperature difference, low-density cement slurry, the latex is styrene-butadiene latex; the defoamer is a liquid mixed with tributyl phosphate and silicone defoamer in a mass ratio of 1:1.
[0026] On the other hand, the present invention also provides a method for preparing the above-mentioned high temperature resistant, large temperature difference, low density cement slurry, which is characterized by comprising: mixing G-grade oil well cement, lightening agent, filling material, fluid loss reducer, retarder, latex, defoaming agent and water according to a proportion.
[0027] In another aspect, the present invention further provides the use of the above-mentioned high temperature resistant, large temperature difference, low density cement slurry in cementing operations.
[0028] The technical solution of the present invention has the following beneficial effects:
[0029] (1) The high temperature resistant large temperature difference low density cement slurry of the present invention is suitable for cementing at high temperature of 160°C and large temperature difference of less than 120°C, and the density is 1.3-1.5g / cm 3 Adjustable, good stability under high temperature conditions, adjustable thickening time, and obvious advantages in the development speed of top strength over large temperature differences;
[0030] (2) The high temperature resistant large temperature difference low density cement slurry of the present invention has the advantages of low viscosity, good fluidity and high mixing efficiency, which is beneficial to reducing mold resistance and preventing pressure leakage in the formation during cementing, and at the same time has good anti-gas channeling and increased elastic toughness performance;
[0031] (3) The fluid loss reducer used in the present invention is a large temperature difference fluid loss reducer, which has the performance of improving the strength development of cement paste and can effectively improve the strength development of the top of cement paste under large temperature difference conditions;
[0032] (4) The retarder used in the present invention is a large temperature difference retarder, which has the advantages of strong high temperature resistance and rapid development of top strength under large temperature difference. DETAILED DESCRIPTION
[0033] In order to fully understand the purpose, features and effects of the present invention, the present invention is described in detail through the following specific embodiments. Except for the following contents, the process method of the present invention adopts conventional methods or devices in the art. Unless otherwise specified, the following terms have the meanings commonly understood by those skilled in the art.
[0034] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe a feature or characteristic, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0035] A high temperature resistant and large temperature difference low density cement slurry comprises: G-class oil well cement, a lightening agent, a filling material, a fluid loss reducing agent, a retarder, latex, a defoaming agent and water.
[0036] G-grade oil well cement is the main gelling component of low-density cement slurry; the role of the lightener is to reduce water consumption, reduce water-cement ratio, reduce cement slurry density and increase cement slurry solid content, and it is a key component of low-density cement slurry; the filling material has different particle sizes and activities, and is filled into the low-density cement slurry, which has a particle grading effect, and can improve the suspension stability of low-density cement slurry at high temperatures. At the same time, through material proportioning, it improves the problem that high-activity cementing materials are prone to shortening the thickening time and increasing the amount of retarder at high temperatures; the main function of the fluid loss reducer is to control the water loss of cement slurry, increase the liquid phase viscosity of cement slurry, and improve the high-temperature suspension stability. At the same time, its molecular structure design Specifically targeting the temperature difference effect, it improves the development of top strength; the retarder has a good retarding effect at high temperature, and is also beneficial to the development of top strength. When used together with a fluid loss reducer, it can effectively improve the development of top strength under large temperature difference conditions; latex has the characteristics of improving cement slurry water loss and improving high-temperature suspension stability. In this cement slurry, it can reduce the amount of cement slurry fluid loss reducer, reduce the viscosity of the cement slurry phase, while maintaining good suspension stability, improve the mixing ability and rheology of the cement slurry, and have good anti-gas channeling and increased elasticity and toughness properties; the defoamer is mainly used to eliminate and avoid foaming during the mixing process of cement slurry, and improve the mixing efficiency of cement slurry.
[0037] The components of the high temperature resistant, large temperature difference, low density cement slurry of the present invention are introduced in detail below:
[0038] G-grade oil well cement
[0039] G-grade oil well cement is a highly sulfate-resistant G-grade oil well cement.
[0040] Grade G oil well cement is the main gelling component of low-density cement slurry, which solidifies to form strength and seal the annulus between the formation and the casing.
[0041] Lightening Agent
[0042] The function of lightener is to reduce water consumption, reduce water-cement ratio, reduce cement slurry density and increase cement slurry solid content. It is a key component of low-density cement slurry.
[0043] In some preferred embodiments, the lightening agent used in the present invention is a low-density lightening agent. The low-density lightening agent has a pressure bearing capacity of 10000-25000 psi and a density of 0.6±0.2 g / cm 3 Artificial glass beads.
[0044] In some preferred embodiments, based on 100 parts by weight of Class G oil well cement, the ratio of the lightening agent is 8-35 parts by weight.
[0045] When the ratio of the lightening agent is less than the minimum value of the above range, the water-cement ratio of the cement slurry is large, and the stability and strength of the cement slurry are poor; when the ratio of the lightening agent is greater than the maximum value of the above range, the solid content of the cement slurry is too high, the cement slurry is difficult to mix and the fluidity is poor; the ratio of the lightening agent is directly related to the design density of the cement slurry. The lower the design density of the cement slurry, the higher the ratio of the lightening agent, and the higher the design density of the cement slurry, the lower the ratio of the lightening agent.
[0046] Further preferably, based on 100 parts by weight of Class G oil well cement, the ratio of the lightening agent is 10-32 parts by weight.
[0047] In a preferred embodiment, the cement slurry density range is 1.3 g / cm 3 Up to 1.5g / cm 3 When the cement slurry design density is 1.3g / cm 3 When the ratio of the lightening agent is 25-32 parts by weight, the design density of the cement slurry is 1.4g / cm 3 When the ratio of the lightening agent is 20-28 parts by weight, the design density of the cement slurry is 1.5g / cm 3 When the ratio of the lightening agent is 10-18 parts by weight.
[0048] Filling material
[0049] The filling material used in the present invention is a low-density filling material, which can form a particle grading effect with cement particles and artificial microbeads, improve the suspension stability of cement slurry and the mixing ability of cement slurry, have stable performance under high temperature conditions, will not cause the retarder to fail due to excessive activity, thereby shortening the thickening time, and can reduce the amount of retarder used, which is beneficial to increasing the development speed of the top strength. At the same time, it has a higher silica content, which can improve the high-temperature strength decay problem of cement.
[0050] In some preferred embodiments, the filling material comprises fly ash, microsilica, ultrafine cement and silica powder in a mass ratio of 5-25:5-45:5-30:10-55.
[0051] Further preferably, the fly ash density is between 2.0-2.6 g / cm 3 The microsilicon has a particle size between 0.05-0.5 μm and a density between 2.0-2.4 g / cm 3 Amorphous silica; the particle size of the ultrafine cement is between 0.5-10 μm and the density is between 2.5-3.2 g / cm 3 The silicon powder has a mesh size between 800-1000 mesh and a density between 2.5-2.8 g / cm 3 Natural quartz powder.
[0052] In some preferred embodiments, based on 100 parts by weight of Class G oil well cement, the proportion of the filler material is 8-45 parts by weight.
[0053] When the ratio of the filling material is less than the minimum value of the above range, the high-temperature suspension stability of the cement slurry is poor and the high-temperature strength is easy to decline; when the ratio of the filling material is greater than the maximum value of the above range, the mixing ability and high-temperature suspension stability of the cement slurry are poor, which is not conducive to high-temperature thickening performance. When the temperature is low, the ratio of the filling material can be appropriately reduced.
[0054] Further preferably, based on 100 parts by weight of Class G oil well cement, the proportion of the filler material is 10-40 parts by weight.
[0055] Fluid Loss Additive
[0056] The main function of fluid loss reducer is to control water loss of cement slurry, increase the liquid phase viscosity of cement slurry, and improve high-temperature suspension stability. At the same time, its molecular structure is designed specifically for the temperature difference effect to improve the development of top strength.
[0057] In some preferred embodiments, the fluid loss reducer used in the present invention is a large temperature difference fluid loss reducer, which is specifically prepared by the following method:
[0058] (1) adding 2-acrylamido-2-methylpropanesulfonic acid, sodium hydroxide, nonionic monomer, carboxylic acid monomer, cationic monomer, crosslinking agent and molecular weight regulator to deionized water in sequence, stirring and mixing, heating and passing inert gas;
[0059] (2) adding ammonium persulfate solution dropwise, and after the reaction temperature stabilizes, heating is continued to react to obtain a fluid loss reducer.
[0060] Further preferably, in parts by weight, the deionized water is 100 parts by weight; the 2-acrylamido-2-methylpropane sulfonic acid is 15-30 parts by weight; the nonionic monomer is 2-10 parts by weight; the carboxylic acid monomer is 0.1-5 parts by weight; the cationic monomer is 0.1-5 parts by weight; the cross-linking agent is 0.001-0.1 parts by weight; the ammonium persulfate is 0.1-2 parts by weight, the sodium hydroxide is 3-10 parts by weight, and the molecular weight regulator is 0.1-1 parts by weight.
[0061] Preferably, the nonionic monomer is one or more of acrylamide, N,N-dimethylacrylamide, N-hydroxymethylacrylamide, and 4-acryloylmorpholine, thereby improving the adsorption of the polymer and reducing the influence of the polymer on the thickening time and strength of the cement slurry.
[0062] Preferably, the carboxylic acid monomer is one or more of acrylic acid, maleic anhydride and itaconic acid, thereby improving the adsorption of the polymer and the ability to control water loss at high temperature.
[0063] Preferably, the cationic monomer is one or more of methacryloyloxyethyltrimethylammonium chloride, methacryloylpropyltrimethylammonium chloride, and dimethyldiallylammonium chloride, thereby improving the resistance of the polymer to metal ions and preventing the metal ions from complexing with polymer molecules and affecting the fluidity of cement slurry.
[0064] Preferably, the crosslinking agent is one or more of diacetone acrylamide, N,N-methylenebisacrylamide, pentaerythritol triallyl ether, and trimethylolpropane triacrylate, thereby forming a certain structure of the polymer molecules, thereby improving the molecular weight and temperature resistance.
[0065] Preferably, the molecular weight regulator is one or more of tert-dodecyl mercaptan, isooctyl 3-mercaptopropionate, sodium vinyl sulfonate, sodium methacrylate sulfonate, and sodium formate, thereby controlling the molecular weight of the polymer.
[0066] In the present invention, the fluid loss reducer needs to be used in combination with latex or other auxiliary fluid loss reducing materials under high temperature conditions. Compared with similar high-temperature fluid loss reducers, it optimizes the large temperature difference performance and can effectively improve the top strength of low-density cement slurry.
[0067] In some preferred embodiments, based on 100 parts by weight of Class G oil well cement, the ratio of the fluid loss additive is 5-20 parts by weight.
[0068] When the ratio of the fluid loss agent is less than the minimum value of the above range, the water loss of the cement slurry is large, the liquid phase viscosity is low, and it is easy to cause the cement slurry to thicken and become poor in stability; when the ratio of the fluid loss agent is greater than the maximum value of the above range, the mixing ability of the cement slurry is poor, the liquid phase viscosity is high, and the fluidity is poor.
[0069] Further preferably, based on 100 parts by weight of Class G oil well cement, the ratio of the fluid loss additive is 5-15 parts by weight.
[0070] Retarder
[0071] The retarder used in the present invention is a large temperature difference retarder, which can effectively prolong the thickening time at high temperature. On the basis of significantly prolonging the dynamic setting time of cement slurry, it improves the static gelling effect of cement slurry and has a good promoting effect on the development of strength of cement slurry in a static state. Compared with similar retarders, under the condition of similar thickening time, the strength development of cement slurry under top temperature conditions is significantly accelerated.
[0072] In some preferred embodiments, the retarder used in the present invention is prepared by the following method:
[0073] (1) adding 2-acrylamido-2-methylpropanesulfonic acid, a rigid monomer, a carboxylic acid monomer, an ether monomer, a crosslinking agent, and a molecular weight regulator to deionized water in sequence, stirring and mixing, heating, and introducing an inert gas;
[0074] (2) adding ammonium persulfate solution and tetraethylenepentamine solution dropwise successively, and after the reaction temperature stabilizes, heating is continued to react to obtain a retarder.
[0075] Further preferably, in parts by weight, the deionized water is 100 parts by weight; the 2-acrylamido-2-methylpropane sulfonic acid is 15-50 parts by weight; the carboxylic acid monomer is 2-15 parts by weight; the rigid monomer is 0.5-10 parts by weight; the ether monomer is 0.1-5 parts by weight; the cross-linking agent is 0.02-2 parts by weight; the molecular weight regulator is 0-5 parts by weight; the ammonium persulfate is 0.2-2 parts by weight; and the tetraethylenepentamine is 0.2-2 parts by weight.
[0076] Preferably, the carboxylic acid monomer is one or more of acrylic acid, maleic anhydride and itaconic acid, thereby improving the adsorption of the polymer and prolonging the thickening time of the cement slurry.
[0077] Preferably, the rigid monomer is one or more of sodium styrene sulfonate, N,N-dimethylacrylamide, and N-hydroxymethylacrylamide, thereby increasing the rigidity of the long-chain polymer molecules, improving their high temperature resistance, and reducing temperature sensitivity.
[0078] Preferably, the ether monomer is one or more of allyl polyoxyethylene ether-1200, allyl polyoxyethylene ether-2400, allyl polyoxyethylene ether-3600, methyl allyl polyoxyethylene ether-1200, methyl allyl polyoxyethylene ether-2400, methyl allyl polyoxyethylene ether-3600, isopentanol polyoxyethylene ether-1200, isopentanol polyoxyethylene ether-2400, and isopentanol polyoxyethylene ether-3600. The ether monomer used in the present invention has a long side chain structure, which can form a steric hindrance effect and improve adsorption, and can enhance the retarding effect at high temperature. At the same time, it has a certain hydrophobic association effect, which is beneficial to the static gelation of cement slurry and improves strength development.
[0079] Preferably, the crosslinking agent is one or more of diacetone acrylamide, polyethylene glycol diacrylate-400, trimethylolpropane triacrylate, and ethylene glycol diallyl ether, thereby allowing the polymer molecules to form a certain structure, improving the temperature resistance and enhancing the high-temperature retarding effect.
[0080] Preferably, the molecular weight regulator is one or more of tert-dodecyl mercaptan, isooctyl 3-mercaptopropionate, sodium vinyl sulfonate, sodium methacrylic sulfonate, and sodium formate, thereby controlling the molecular weight of the polymer.
[0081] In some preferred embodiments, based on 100 parts by weight of Class G oil well cement, the retarder is contained in an amount of 0-10 parts by weight.
[0082] When the retarder ratio is less than the minimum value in the above range, the high-temperature thickening time of the cement slurry is short and does not meet the construction safety time; when the retarder ratio is greater than the maximum value in the above range, the high-temperature thickening time of the cement slurry is long and the strength development is slow.
[0083] Further preferably, based on 100 parts by weight of Class G oil well cement, the retarder is mixed in a ratio of 0-8 parts by weight.
[0084] latex
[0085] As an auxiliary fluid loss reducer, latex can effectively improve the water loss control ability and high-temperature suspension stability of low-density cement slurry, reduce the dosage of some fluid loss reducers, improve the mixing ability and fluidity of cement slurry, and at the same time have good anti-gas channeling and increased elasticity and toughness properties.
[0086] In some preferred embodiments, the latex is styrene-butadiene latex.
[0087] In some preferred embodiments, based on 100 parts by weight of Class G oil well cement, the latex is contained in an amount of 0-20 parts by weight.
[0088] When the latex ratio is less than the minimum value of the above range, the cement slurry loses more water and has poor suspension stability; when the latex ratio is greater than the maximum value of the above range, the cement slurry has poor mixing ability and fluidity, and the cement stone has poor compressive strength.
[0089] Further preferably, based on 100 parts by weight of Class G oil well cement, the proportion of the latex is 0-18 parts by weight.
[0090] Defoaming agent
[0091] Defoaming agents are mainly used to eliminate and avoid foaming during cement slurry mixing and improve cement slurry mixing efficiency.
[0092] In some preferred embodiments, the defoaming agent is a mixture of tributyl phosphate and silicone defoaming agent in a mass ratio of 1:1.
[0093] In some preferred embodiments, based on 100 parts by weight of Class G oil well cement, the defoaming agent is mixed in an amount of 0.5-3 parts by weight.
[0094] When the ratio of the defoaming agent is less than the minimum value of the above range, the cement slurry foam cannot be effectively removed; when the ratio of the defoaming agent is greater than the maximum value of the above range, the defoaming rate will not be further improved.
[0095] Further preferably, based on 100 parts by weight of Class G oil well cement, the defoaming agent is mixed in an amount of 0.5-2.5 parts by weight.
[0096] In the present invention, according to the density design of cement slurry, the lightening agent and the filling material can be adjusted to different proportions to meet the cement slurry performance with different density requirements and performance differences of different batches of materials to meet the on-site requirements. When the cement slurry design density is low, the ratio of the lightening agent and the filling material should be increased to balance the water-cement ratio and improve the stability of the low-density cement slurry; when the cement slurry density design is high, the ratio of the lightening agent and the filling material should be reduced accordingly to improve the mixing performance and fluidity of the cement slurry. The ratio of the filling material is adjusted according to the temperature. When the temperature is high, the ratio of the filling material is increased to meet the requirements of high-temperature suspension stability and high-temperature strength decay; when the temperature is low, the ratio of the filling material is reduced to meet the mixing performance and strength development at low temperatures. The performance of cement slurry, especially high-temperature suspension stability, is related to a variety of materials. In addition to the lightening agent and the filling material, the amount of the water loss reducer and the latex should not only meet the water loss performance requirements, but also contribute to the high-temperature suspension stability and fluidity. The amount of the retarder is selected according to the required temperature and thickening time. The amount of defoamer is selected according to the amount of latex added and the foaming degree of cement slurry, and water is added according to the design density of cement slurry and the amount of other admixtures added to ensure that the actual density of cement slurry meets the design. The entire low-density cement slurry system must meet the mixing efficiency, rheological properties, water loss properties, suspension stability, thickening time performance and strength development performance required for cementing operations.
[0097] On the other hand, the present invention provides a method for preparing the high temperature resistant, large temperature difference, low density cement slurry, characterized in that it comprises: mixing G-grade oil well cement, lightening agent, filling material, fluid loss reducer, retarder, latex, defoaming agent and water according to a proportion.
[0098] In another aspect, the present invention further provides the use of the high temperature resistant, large temperature difference, low density cement slurry in cementing operations.
[0099] Example
[0100] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions. The raw materials used in the following examples are all conventionally purchased.
[0101] Example 1: Preparation of fluid loss additive
[0102] Weigh a certain weight of reactants: 200 g of deionized water, 45.64 g of 2-acrylamido-2-methylpropanesulfonic acid, 8.92 g of sodium hydroxide, 4.85 g of N,N-dimethylacrylamide, 2.23 g of acrylic acid, 2.65 g of methacryloylpropyltrimethylammonium chloride, 0.12 g of pentaerythritol triallyl ether, and 0.40 g of sodium formate, add them into a reaction container in sequence, stir and mix evenly, and control the stirring speed at 120 r / min;
[0103] The reaction vessel was placed in a water bath, heated to 56°C, and nitrogen was introduced for 10 min to replace the oxygen therein;
[0104] Prepare 8.40 g of 10% ammonium persulfate solution, add dropwise to initiate polymerization reaction, and after the reaction temperature stabilizes, raise the temperature to 85° C. and keep the reaction for 4 hours to obtain a fluid loss reducer.
[0105] Example 2: Preparation of fluid loss additive
[0106] Weigh a certain weight of reactants: 250 g of deionized water, 37.86 g of 2-acrylamido-2-methylpropanesulfonic acid, 7.62 g of sodium hydroxide, 10.2 g of N-hydroxymethyl acrylamide, 1.05 g of maleic anhydride, 5.62 g of dimethyldiallylammonium chloride, 0.05 g of N,N-methylenebisacrylamide, and 0.08 g of sodium methyl propene sulfonate, add them into the reaction container in sequence, stir and mix evenly, and control the stirring speed at 120 r / min;
[0107] Place the reaction vessel in a water bath, heat to 60°C, and introduce nitrogen for 10 min to replace the oxygen in it;
[0108] Prepare 12.28 g of 10% ammonium persulfate solution, add dropwise to initiate polymerization reaction, and after the reaction temperature stabilizes, raise the temperature to 83° C. and keep the reaction for 4 hours to obtain a fluid loss reducer.
[0109] Example 3: Preparation of fluid loss additive
[0110] Weigh a certain weight portion of reactants: 220 g of deionized water, 56.74 g of 2-acrylamido-2-methylpropanesulfonic acid, 12.68 g of sodium hydroxide, 20.82 g of 4-acryloylmorpholine, 5.75 g of maleic anhydride, 1.62 g of methacryloylpropyltrimethylammonium chloride, 0.21 g of trimethylolpropane triacrylate, and 0.55 g of tert-dodecyl mercaptan, add them into a reaction container in sequence, stir and mix evenly, and control the stirring speed at 120 r / min;
[0111] Place the reaction vessel in a water bath, heat to 52°C, and introduce nitrogen for 10 min to replace the oxygen in it;
[0112] Prepare 14.56 g of 10% ammonium persulfate solution, add dropwise to initiate polymerization reaction, and after the reaction temperature stabilizes, raise the temperature to 80° C. and keep the reaction for 4 hours to obtain a fluid loss reducer.
[0113] Example 4: Preparation of retarder
[0114] Weigh a certain weight portion of reactants: deionized water 110g, 2-acrylamido-2-methylpropanesulfonic acid 26.15g, N-hydroxymethyl acrylamide 3.42g, itaconic acid 7.16g, isopentanol polyoxyethylene ether-24002.24g, polyethylene glycol diacrylate-400 0.52g, sodium methacrylate sulfonate 0.02g, add them into the reaction container in sequence, stir and mix evenly, and control the stirring speed at 120r / min;
[0115] Place the reaction vessel in a water bath, heat to 60°C, and introduce nitrogen for 10 min to replace the oxygen in it;
[0116] Prepare 6.50 g of 10% ammonium persulfate solution and 4.60 g of 10% tetraethylenepentamine solution, add them dropwise successively to initiate polymerization reaction. After the reaction temperature stabilizes, raise the temperature to 82°C and keep the reaction for 4 hours to obtain a retarder.
[0117] Example 5: Preparation of retarder
[0118] Weigh a certain weight of reactants: 150 g of deionized water, 35.45 g of 2-acrylamido-2-methylpropanesulfonic acid, 12.24 g of N,N-dimethylacrylamide, 20.46 g of maleic anhydride, 9.32 g of methyl allyl polyoxyethylene ether-3600, 0.04 g of trimethylolpropane triacrylate, and 0.14 g of sodium formate, add them into the reaction container in sequence, stir and mix evenly, and control the stirring speed at 120 r / min;
[0119] Place the reaction vessel in a water bath, heat to 55°C, and introduce nitrogen for 10 min to replace the oxygen in it;
[0120] Prepare 8.45 g of 10% ammonium persulfate solution and 6.80 g of 10% tetraethylenepentamine solution, add them dropwise successively to initiate polymerization reaction. After the reaction temperature stabilizes, raise the temperature to 85°C and keep the reaction for 4 hours to obtain a retarder.
[0121] Example 6: Preparation of retarder
[0122] Weigh a certain weight portion of reactants: deionized water 130g, 2-acrylamido-2-methylpropanesulfonic acid 30.46g, sodium styrene sulfonate 2.41g, itaconic acid 14.86g, allyl polyoxyethylene ether-2400 4.65g, ethylene glycol diallyl ether 0.16g, tert-dodecyl mercaptan 0.36g, add them into the reaction container in sequence, stir and mix evenly, and control the stirring speed at 120r / min;
[0123] The reaction vessel was placed in a water bath, heated to 58°C, and nitrogen was introduced for 10 min to replace the oxygen therein;
[0124] Prepare 5.66g of 10% ammonium persulfate solution and 5.24g of 10% tetraethylenepentamine solution, add them dropwise successively to initiate polymerization reaction. After the reaction temperature stabilizes, raise the temperature to 80°C and keep the reaction for 4 hours to obtain a retarder.
[0125] Example 7: Preparation of high temperature resistant, large temperature difference, low density cement slurry
[0126] Weigh the solid components: 300g G-grade oil well cement, 93g lightener (artificial glass microspheres, pressure bearing capacity 10000psi, density 0.6g / cm 3 ), 30g filling material (a mixture of fly ash, microsilicon, ultrafine cement, and silica fume in a weight ratio of 4:3:1:4, with a fly ash density of 2.4g / cm 3 The particle size of microsilicon is 0.15 μm and the density is 2.2 g / cm 3 The particle size of ultrafine cement is 10μm and the density is 2.9g / cm 3 , the mesh number of silicon powder is 800 mesh and the density is 2.65g / cm 3 );
[0127] Weigh the liquid components: 238.4 g of water, 36 g of a fluid loss reducer (Example 1), 4.8 g of a retarder (Example 4), and 3 g of a composite defoamer of tributyl phosphate and polydimethylsiloxane in a mass ratio of 1:1;
[0128] Mix and prepare cement slurry according to API standard to obtain a density of 1.3g / cm 3 Low-density cement slurry, which is suitable for cementing operations at temperatures below 100°C.
[0129] Example 8: Preparation of high temperature resistant, large temperature difference, low density cement slurry
[0130] Weigh the solid components: 400g G-grade oil well cement, 48g lightener (artificial glass microspheres, pressure bearing capacity 15000psi, density 0.6g / cm 3 ), 112 g of filling material (same as in Example 7);
[0131] Weigh the liquid components: 288.1 g of water, 24 g of a fluid loss reducer (Example 2), 32 g of styrene-butadiene latex, 12 g of a retarder (Example 5), and 6.4 g of a composite defoamer of tributyl phosphate and polydimethylsiloxane in a mass ratio of 1:1;
[0132] Mix and prepare cement slurry according to API standard to obtain a density of 1.5g / cm 3 Low-density cement slurry, this cement slurry is suitable for high-temperature and large temperature difference cementing operations under conditions below 130°C.
[0133] Example 9: Preparation of high temperature resistant, large temperature difference, low density cement slurry
[0134] Weigh the solid components: 330g G-grade oil well cement, 69.3g lightener (artificial glass microspheres, pressure bearing capacity 25000psi, density 0.62g / cm 3 ), 115.5 g of filling material (same as in Example 7);
[0135] Weigh the liquid components: 274.5 g of water, 26.4 g of fluid loss reducer (Example 3), 29.7 g of styrene-butadiene latex, 16.5 g of retarder (Example 6), and 6.6 g of a composite defoamer of tributyl phosphate and polydimethylsiloxane in a mass ratio of 1:1;
[0136] Mix and prepare cement slurry according to API standard to obtain a density of 1.4g / cm 3 Low-density cement slurry is suitable for high-temperature and large temperature difference cementing operations under conditions below 160°C.
[0137] Performance Testing
[0138] In order to verify the performance of the fluid loss reducer, retarder and high temperature and large temperature difference resistant low density cement slurry of the present invention, the inventors conducted performance tests on them. Among them, the static filtration, rheological properties, thickening time, compressive strength, upper and lower density difference tests were all measured in accordance with the provisions of GB / T 19139-2012 "Test Methods for Oil Well Cement".
[0139] 1.1 Performance test of fluid loss additive
[0140] The fluid loss reducer prepared in Example 1 was used for a comparative experiment with the existing fluid loss reducer C-FL80L. Cement slurries were prepared according to cement slurry formulas 1 and 2. Formula 2 was a comparative experiment of formula 1. The cement slurry density was 1.9 g / cm 3 , the comparison results are shown in Table 1.
[0141] Formula 1: 100% "G" grade cement + 4% fluid loss reducer + 0.4% retarder (C-R21L) + 0.4% defoamer (C-DF60L) + 38.95% fresh water; cement slurry density is 1.9g / cm 3 .
[0142] Formula 2: 100% "G" grade cement + 4% fluid loss reducer (C-FL80L) + 0.4% retarder (C-R21L) + 0.4% defoamer (C-DF60L) + 38.95% fresh water; cement slurry density is 1.9g / cm 3 .
[0143] Table 1 Performance comparison between fluid loss reducer and fluid loss reducer C-FL80L
[0144]
[0145] From the results in Table 1 above, it can be seen that compared with the conventional fluid loss reducer C-FL80L, the fluid loss reducer has the advantage of fast strength development. Under the condition of similar thickening time, the cement slurry prepared with the fluid loss reducer has significantly improved both the top strength and the bottom strength.
[0146] 1.2 Performance test of retarder
[0147] A control experiment was conducted using the retarder prepared in Example 4 and the existing high-temperature retarder C-R42L. Cement slurries were prepared according to cement slurry formulas 3 and 4. Formula 4 was a control experiment of Formula 3. The comparison results are shown in Table 2.
[0148] Formula 3: 100% "G" grade cement + 35% silica fume + 6% fluid loss reducer (C-FL80L) + 2.5% retarder + 0.5% defoamer (C-DF60L) + 48.02% fresh water; cement slurry density is 1.9g / cm 3 .
[0149] Formula 4 (comparative formula): 100% "G" grade cement + 35% silica fume + 6% fluid loss reducer (C-FL80L) + 2.5% high temperature retarder (C-R42L) + 0.5% defoamer (C-DF60L) + 48.02% fresh water; cement slurry density is 1.9g / cm 3 .
[0150] Table 2 Performance comparison between retarder and high temperature retarder C-R42L
[0151]
[0152] From the results in Table 2 above, it can be seen that when the thickening time is similar, the top strength of the retarder develops significantly faster.
[0153] 1.3 Performance test of high temperature resistance, large temperature difference and low density cement slurry
[0154] The performance of the high temperature resistant, large temperature difference, low density cement slurry of the present invention was evaluated, and the application conditions and performance evaluation results are shown in Tables 3 and 4.
[0155] Table 3 Application conditions of high temperature resistant, large temperature difference and low density cement slurry
[0156]
[0157] Table 4 Performance evaluation of high temperature resistance, large temperature difference and low density cement slurry
[0158]
[0159] It can be seen from the results in Tables 3 and 4 that the high-temperature and large temperature difference low-density cement slurry of the present invention has good stability and top strength development under high temperature conditions of 156°C and temperature differences of 66°C and 106°C, as well as good performances such as low API water loss, adjustable high-temperature thickening time and good fluidity.
[0160] The present invention has been disclosed above with preferred embodiments, but those skilled in the art should understand that these embodiments are only used to describe the present invention and should not be understood as limiting the scope of the present invention. It should be noted that all changes and substitutions equivalent to these embodiments should be deemed to be included in the scope of the claims of the present invention. Therefore, the scope of protection of the present invention should be based on the scope defined in the claims.
Claims
1. A high temperature resistant, large temperature difference, low density cement slurry, characterized in that: include: Class G oil well cement, lightening agent, filling material, fluid loss additive, retarder, latex, defoaming agent and water.
2. The high temperature resistant, large temperature difference, low density cement slurry according to claim 1, characterized in that: The invention comprises, by weight: 100 parts by weight of G-grade oil well cement; 8-35 parts by weight of lightening agent; 8-45 parts by weight of filling material; 5-20 parts by weight of fluid loss reducing agent; 0-10 parts by weight of retarder; 0-20 parts by weight of latex; 0.5-3 parts by weight of defoaming agent; and 50-100 parts by weight of fresh water.
3. The high temperature resistant, large temperature difference, low density cement slurry according to claim 1, characterized in that: The lightening agent is artificial glass microspheres, the pressure bearing capacity of the artificial glass microspheres is 10000-25000psi, and the density is 0.6±0.2g / cm 3 .
4. The high temperature resistant, large temperature difference, low density cement slurry according to claim 1, characterized in that: The filling materials are fly ash, microsilica, ultrafine cement and silica powder in a mass ratio of 5-25:5-45:5-30:10-55.
5. The high temperature resistant, large temperature difference, low density cement slurry according to claim 4, characterized in that: The fly ash density is between 2.0-2.6 g / cm 3 The microsilicon has a particle size between 0.05-0.5 μm and a density between 2.0-2.4 g / cm 3 Amorphous silica; the particle size of the ultrafine cement is between 0.5-10 μm and the density is between 2.5-3.2 g / cm 3 The silicon powder has a mesh size between 800-1000 mesh and a density between 2.5-2.8 g / cm 3 Natural quartz powder.
6. The high temperature resistant, large temperature difference, low density cement slurry according to claim 1, characterized in that: The fluid loss reducer is prepared by the following method: (1) adding 2-acrylamido-2-methylpropanesulfonic acid, sodium hydroxide, nonionic monomer, carboxylic acid monomer, cationic monomer, crosslinking agent and molecular weight regulator to deionized water in sequence, stirring and mixing, heating and passing inert gas; (2) adding ammonium persulfate solution dropwise, and after the reaction temperature stabilizes, heating is continued to react to obtain a fluid loss reducer.
7. The high temperature resistant, large temperature difference, low density cement slurry according to claim 6, characterized in that: In parts by weight, the deionized water is 100 parts by weight; the 2-acrylamido-2-methylpropane sulfonic acid is 15-30 parts by weight; the nonionic monomer is 2-10 parts by weight; the carboxylic acid monomer is 0.1-5 parts by weight; the cationic monomer is 0.1-5 parts by weight; the cross-linking agent is 0.001-0.1 parts by weight; the ammonium persulfate is 0.1-2 parts by weight, the sodium hydroxide is 3-10 parts by weight, and the molecular weight regulator is 0.1-1 parts by weight.
8. The high temperature resistant, large temperature difference, low density cement slurry according to claim 6, characterized in that: The nonionic monomer is one or more of acrylamide, N,N-dimethylacrylamide, N-hydroxymethylacrylamide, and 4-acryloylmorpholine; the carboxylic acid monomer is one or more of acrylic acid, maleic anhydride, and itaconic acid.
9. The high temperature resistant, large temperature difference, low density cement slurry according to claim 6, characterized in that: The cationic monomer is one or more of methacryloyloxyethyl trimethyl ammonium chloride, methacryloyl propyl trimethyl ammonium chloride, and dimethyl diallyl ammonium chloride; the crosslinking agent is one or more of diacetone acrylamide, N,N-methylenebisacrylamide, pentaerythritol triallyl ether, and trimethylolpropane triacrylate; the molecular weight regulator is one or more of tert-dodecyl mercaptan, isooctyl 3-mercaptopropionate, sodium vinyl sulfonate, sodium methacrylic acid, and sodium formate.
10. The high temperature resistant, large temperature difference, low density cement slurry according to claim 1, characterized in that: The retarder is prepared by the following method: (1) adding 2-acrylamido-2-methylpropanesulfonic acid, a rigid monomer, a carboxylic acid monomer, an ether monomer, a crosslinking agent, and a molecular weight regulator to deionized water in sequence, stirring and mixing, heating, and introducing an inert gas; (2) adding ammonium persulfate solution and tetraethylenepentamine solution dropwise successively, and after the reaction temperature stabilizes, heating is continued to react to obtain a retarder.
11. The high temperature resistant, large temperature difference, low density cement slurry according to claim 10, characterized in that: In parts by weight, the deionized water is 100 parts by weight; the 2-acrylamido-2-methylpropane sulfonic acid is 15-50 parts by weight; the carboxylic acid monomer is 2-15 parts by weight; the rigid monomer is 0.5-10 parts by weight; the ether monomer is 0.1-5 parts by weight; the cross-linking agent is 0.02-2 parts by weight; the molecular weight regulator is 0-5 parts by weight; the ammonium persulfate is 0.2-2 parts by weight; and the tetraethylenepentamine is 0.2-2 parts by weight.
12. The high temperature resistant, large temperature difference, low density cement slurry according to claim 10, characterized in that: The carboxylic acid monomer is one or more of acrylic acid, maleic anhydride and itaconic acid; the rigid monomer is one or more of sodium styrene sulfonate, N,N-dimethylacrylamide and N-hydroxymethylacrylamide.
13. The high temperature resistant, large temperature difference, low density cement slurry according to claim 10, characterized in that: The ether monomer is one or more of allyl polyoxyethylene ether-1200, allyl polyoxyethylene ether-2400, allyl polyoxyethylene ether-3600, methyl allyl polyoxyethylene ether-1200, methyl allyl polyoxyethylene ether-2400, methyl allyl polyoxyethylene ether-3600, isopentanol polyoxyethylene ether-1200, isopentanol polyoxyethylene ether-2400, and isopentanol polyoxyethylene ether-3600.
14. The high temperature resistant, large temperature difference, low density cement slurry according to claim 10, characterized in that: The cross-linking agent is one or more of diacetone acrylamide, polyethylene glycol diacrylate-400, trimethylolpropane triacrylate, and ethylene glycol diallyl ether; the molecular weight regulator is one or more of tert-dodecyl mercaptan, isooctyl 3-mercaptopropionate, sodium vinyl sulfonate, sodium methacrylate sulfonate, and sodium formate.
15. The high temperature resistant, large temperature difference, low density cement slurry according to claim 1, characterized in that: The latex is styrene-butadiene latex; the defoamer is a liquid mixed with tributyl phosphate and silicone defoamer in a mass ratio of 1:
1.
16. The method for preparing high temperature resistant large temperature difference low density cement slurry according to any one of claims 1 to 15, characterized in that: include: The G-grade oil well cement, lightening agent, filling material, fluid loss additive, retarder, latex, defoaming agent and water are mixed according to the proportion.
17. Use of the high temperature resistant, large temperature difference, low density cement slurry according to any one of claims 1 to 15 in cementing operations.